2016
DOI: 10.1016/j.geothermics.2016.06.011
|View full text |Cite
|
Sign up to set email alerts
|

Extracting past atmospheric warming and urban heating effects from borehole temperature profiles

Abstract: Borehole temperature logs in urban areas often show deviation from the regional geothermal gradient that increases towards the land surface in the top ~100 meters. This deviation is the sum of two effects: atmospheric global warming and urban heating. To invert the temperature profiles (T-logs), a novel analytical model is presented to distinguish effects of global warming and of urban structures on the ground thermal regime. The inversion is demonstrated on four characteristic T-logs measured in the city and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
37
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 43 publications
(40 citation statements)
references
References 52 publications
3
37
0
Order By: Relevance
“…With this insight, and in the context of climate change, the development of ground thermal regime in urban areas has to be reviewed. This also concerns the understanding of the evolution of SUHI (Arola and Korkka-Niemi, 2014;Bayer et al, 2016;Ferguson and Woodbury, 2004;Huang et al, 2009) and geothermal potentials of the overheated urban subsurface Zhu et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…With this insight, and in the context of climate change, the development of ground thermal regime in urban areas has to be reviewed. This also concerns the understanding of the evolution of SUHI (Arola and Korkka-Niemi, 2014;Bayer et al, 2016;Ferguson and Woodbury, 2004;Huang et al, 2009) and geothermal potentials of the overheated urban subsurface Zhu et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…Deviations from this distribution can be observed in the case of groundwater flow, varying ground thermal properties and/or anthropogenic effects. The latter results in elevated ground temperatures with zero or negative temperature gradients extending to depths more than 50 m, which is observed worldwide in urban areas [24][25][26][27]. In-situ case studies of temperature borehole logging have revealed increased ground temperatures, which are attributed to the urbanisation effect mainly based on observations of building presence and occupation close to the measurement locations [28][29][30].…”
Section: Introductionmentioning
confidence: 99%
“…Many of the temperature-depth profiles display a warming trend. Such subsurface temperature distribution may be due to land use change, global warming, or groundwater flow (Kohl 1999;Taniguchi et al 1999Taniguchi et al , 2003Huang et al 2000;Pollack and Huang 2000;Ferguson et al 2006;Bense and Beltrami 2007;Verdoya et al 2007;Kataoka et al 2009;Yamano et al 2009;Bayer et al 2016).…”
Section: Present Surface Soil Temperature (Psst) and Land Covermentioning
confidence: 99%
“…Temperature-depth profiles are widely used for reconstructing historical surface temperature in association with climate change (Taniguchi et al 1999;Pollack and Huang 2000;Roy et al 2002;Eppelbaum et al 2006;Balobaev et al 2008;Ouzzaouit et al 2014;Bayer et al 2016). Surface soil temperature change can be obtained from PSST minus ISST which is estimated from temperature-depth profile.…”
Section: Surface Soil Temperature Change and Land Cover Changementioning
confidence: 99%
See 1 more Smart Citation